How much strength the young competitive swimmers are able to transfer from dry land to water? A pilot study - Santos, C. C.; Marinho, D. A.; Costa, M. J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Propulsive force plays a major role in the swimming performance being produced mainly by the upper limbs through the shoulder internal rotation (IR). While the shoulder rotators ´ strength has been widely investigated in young competitive swimmers, the propulsive force mechanism retained little attention (1). Moreover, to our best knowledge, there is not any study aimed to quantify the relative force transfer (RFT) from land to in-water actions. Thus, the aim of this study was to analyze the RFT from land to water in young swimmers at the front-crawl stroke.